Vandalism as a Social Expression: A Theoretical Study of the Dynamics of Individual-Public Space Relations in Railway Infrastructure - Shinta Julianti; Puri Septiana Nursetiyawati; Frida Nurrahma Masturi; Tissa Silvia; Titi Rahmawati (Universitas Budi Luhur, 2025)
Vandalism on railway infrastructure is not merely understood as destructive behavior but also as a form of social expression that reflects the dynamic relationship between individuals and public space. This article examines vandalism as a socially structured phenomenon rooted in social interaction, environmental conditions, and power inequalities within public transportation spaces. The research method in this study is a theoretical study or systematic literature review with a Qualitative-Analytical approach. The data sources in this study are secondary, including sociology and criminology journals that discuss deviation, vandalism, graffiti, public space, and transportation infrastructure. The analysis employs various sociological perspectives, including Anomie Theory to describe collective frustration and weakened normative control; Social Learning Theory to understand peer group influence and the imitation of deviant behavior; Social Control Theory to explore the weakened social bonds that reduce conformity; Conflict Theory to observe vandalism as a symbolic form of resistance against inequality in public space governance; and Social Ecology Theory to highlight the role of environmental disorganization and lack of surveillance in enabling destructive acts. Based on this theoretical mapping, the article argues that vandalism is a multidimensional social phenomenon that requires a comprehensive approach, incorporating not only legal intervention but also strengthened social attachment, community empowerment, and more inclusive public space planning that is responsive to societal needs. It is hoped that this analysis can provide a more comprehensive understanding of the sociological roots of vandalism on railway assets and formulate practical implications for developing more holistic, community-based, and sustainable prevention strategies beyond merely repressive approaches.